Onychodystrophies: possibilities of topical therapy - Irena L. Shlivko; Irina A. Klemenova; Maria S. Neznakhina (Vestnik Dermatologii i Venerologii)
Nail plates are visually significant areas of the body and not only protect the distal phalanges from mechanical damage, but also determine the aesthetic appeal of the hands and feet. Patients with pathological changes in the nails experience not only physical discomfort, but also severe emotional suffering. This determines the search for the most effective methods of treating onychodystrophies. Practitioners are provided with modern information on the etiology, pathogenesis, clinical features of various types of onychodystrophies, therapeutic approaches and methods of local treatment. It is shown that hydration of the nail plate leads to increased permeability of drugs. The use of water-soluble chitosan and other active substances in the treatment of onychodystrophies is justified. As a result of a multicenter observational prospective study to assess the efficacy, safety and tolerability of Klavio lotions for the treatment of non-infectious onychodystrophies of the hands and feet of various etiologies, the effectiveness of these products is demonstrated.